Asymmetric density‐dependent competition and predation between larval salamanders. (7th May 2021) - Anderson, Thomas L.; Burkhart, Jacob J.; Davenport, Jon M.
Abstract: Body size differences among consumers often lead to asymmetric interactions, with larger individuals typically being stronger competitors and/or predators on small individuals. These types of interaction are particularly exemplified in freshwater pond communities, where substantial size variation exists both within and among species of top consumers. We investigated whether density dependence can modify the outcome of size‐structured interactions between larval stages of two pond‐breeding salamanders, Ambystoma annulatum and Ambystoma opacum . Size structure exists in populations of these species due to variation in the timing of breeding, which we hypothesised would amplify predation rates and competitive asymmetries from the early‐arriving species ( A .  annulatum ) on the later‐arriving species ( A .  opacum ). We manipulated the relative densities of both A. annulatum and A .  opacum in outdoor mesocosms. We maintained the experiment through metamorphosis, and analysed size at metamorphosis, larval period length and survival of each species. Ambystoma annulatum imparted a strong density‐dependent effect on A .  opacum through a combination of predation and competition. Survival of A .  opacum was negatively related to the density of A .  annulatum . For the A .  opacum that survived, body size was reduced and larval period lengthened at higher A .  annulatum densities, indicative of interspecific competition that was partly explained by resource pre‐emption. In contrast, A .  annulatum was only affected by intraspecific density‐dependent competition. Our results suggest that density‐dependent effects reinforce asymmetric interactions among larval salamanders. However, the intensity of the asymmetric interactions is mediated by the arrival time and size of conspecifics. Specifically, earlier‐arriving species can negatively affect the later‐arriving species via size‐mediated predation and competition. The interactive effects of density dependence and arrival time of community members are probably a common mechanism generating size variability in ecological communities. Yet, most studies only evaluate one mechanism or the other. By interweaving these two processes, our work displays the importance of understanding context‐dependence in species interactions.